2017
DOI: 10.1109/jcn.2017.000025
|View full text |Cite
|
Sign up to set email alerts
|

Drivingstyles: a mobile platform for driving styles and fuel consumption characterization

Abstract: Intelligent Transportation Systems (ITS) rely on connected vehicle applications to address real-world problems. Research is currently being conducted to support safety, mobility and environmental applications. This paper presents the DrivingStyles architecture, which adopts data mining techniques and neural networks to analyze and generate a classification of driving styles and fuel consumption based on driver characterization. In particular, we have implemented an algorithm that is able to characterize the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…However, the crowdsencing approach presents many risks that could compromise the accuracy, reliability and quality of crowdsensed data, as well as the possibility of providing false information [105]. As for data about driver behavior, the authors of [106] used smartphones combined with the vehicle electronic control unit (ECU) through the on-board diagnostics (OBD-II) Bluetooth interface to collect data about driving characteristics including speed, acceleration, throttle position, and vehicle's geographic position. The data analysis reveals the degree of aggressiveness of drivers and characterizes the different existing driving styles.…”
Section: Smartphonesmentioning
confidence: 99%
“…However, the crowdsencing approach presents many risks that could compromise the accuracy, reliability and quality of crowdsensed data, as well as the possibility of providing false information [105]. As for data about driver behavior, the authors of [106] used smartphones combined with the vehicle electronic control unit (ECU) through the on-board diagnostics (OBD-II) Bluetooth interface to collect data about driving characteristics including speed, acceleration, throttle position, and vehicle's geographic position. The data analysis reveals the degree of aggressiveness of drivers and characterizes the different existing driving styles.…”
Section: Smartphonesmentioning
confidence: 99%
“…As well as the traffic safety, driving style is also important criterion for fuel and energy consumption. By changing driver style, energy and fuel consumption can be reduced [2], [3]. Purpose of analyzing of vehicle data is to observe driver and determine driver behavior.…”
Section: List Of Tablesmentioning
confidence: 99%
“…Recent research has revealed that eco-driving is capable of reducing fuel consumption by an amount ranging from 15% to 25% and GHG emissions by at least 30% [8,10,15,16]. In contrast, the total fuel savings achieved by engines and vehicles of the latest technology is estimated at about 10-12%, which is significantly lower [8].…”
Section: Defining Eco-drivingmentioning
confidence: 99%
“…An aggressive driver is characterized by harsh accelerations and decelerations, while the opposite is true for the careful or cautious one, which is characterized by smooth changes in speed. The main goal of eco-driving is the transition of drivers from aggressive to cautious profile [2], since smoother driving allows fuel savings [16]. Firstly, frequent decelerations cause also frequent accelerations and, thus, more fuel is consumed to increase kinetic energy and restore the vehicle's speed.…”
Section: Eco Driving Effects On Fuel Consumptionmentioning
confidence: 99%